Hak Dan Kedudukan Sebagai Ahli Waris Pengganti dalam Hukum Waris Islam - Samura, Laras Hilda; Franata, Fandy; Gultom, Joshua Hery Cristian; Tarigan, Putri Juliani br (Khazanah : Journal of Islamic Studies, 2023)
Inheritance law is part of the law that has developed and is currently in effect, and reflects the relevant family system. This research is Normative Law research, which is carried out by examining and analyzing legal regulations with legal issues in their consistency with existing principles. Regarding the division of Islamic inheritance, based on the Al-Qur'an, it is a guideline for ijtihad for ulama, as in Indonesia, ijtihad is compiled into regulations compiled in a compilation of Islamic law, strengthened by Presidential Instruction Number 1 of 1991.